The impact of the internal audit on the quality of financial reports in government institutions in the Gaza Strip - MOHAMED ABOU LABAN, HATEM FAWEZI (Journal of Research in Finance and Accounting, 2020)
The study aimed to identify the reality of internal audit in ministries and government institutions operating in the Gaza Strip and to know its impact on the quality of financial reports in ministries and government institutions, in addition to knowing the obstacles to developing internal audit and increasing its effectiveness in achieving its goals. The study reached several results, including:Training of employees in internal audit and internal control is carried out in government institutions and ministries in the Gaza Strip periodically to inform them of the latest methods and techniques used in the field of audit, as well as senior management in government institutions and ministries in the Gaza Strip engages employees in the departments of internal audit and oversight in the development of strategic plans for the institution There are laws and regulations governing internal audits in government institutions and ministries in the Gaza Strip.